Joint analysis of cloud top heights from CloudSat and CALIPSO: New insights into cloud top microphysics. Issue 7 (9th April 2014) - Hagihara, Yuichiro; Okamoto, Hajime; Luo, Zhengzhao Johnny
Abstract: We examined the differences in the cloud top heights (CTHs) detected by the CloudSat radar and Cloud‐Aerosol Lidar and Infrared Pathfinder Satellite Observation (CALIPSO) lidar. Theoretical estimates have shown that CloudSat has higher sensitivity than CALIPSO does when large particles exist. In such case it might be possible that CloudSat‐determined CTHs are larger than CALIPSO‐determined CTHs. We compared the global distribution of CTHs detected by CloudSat and CALIPSO (version 3, V3) using our cloud mask schemes after carefully selecting data during September–November 2006. The global mean fraction of clouds where CloudSat‐determined CTHs were larger than CALIPSO‐determined CTHs turned out to be unexpectedly large. The fractions were 26% and 39% at low level and midlevel, and the corresponding CTH differences were 0.56 km and 0.86 km, respectively. On the western coasts of continents, these clouds occurred within temperature inversions. Accounting for the differences in sensitivity to particle size between CloudSat and CALIPSO, the existence of such clouds indicates that the cloud tops consist of large particles with small number concentration. The discovery of such clouds was revealed by our joint analysis of CloudSat and CALIPSO. When the standard vertical feature mask (VFM) V3 was used, these clouds were also found but the fractions were less pronounced. The differences were partly attributed to the overestimation of cloud fraction in the VFM V3, although the degree of misidentification in V3 was reduced compared with that of V2. Key Points: Examine the CTHs and cloud top microphysics by CloudSat and CALIPSO Clouds where CloudSat‐determined CTHs are larger than CALIPSO ones are revealed Existence of such clouds implies the cloud tops consist of large particles